The Precautionary Principle for Shift-Work Research and Decision-Making. (12th March 2018) - Adams, Charleen D; Blacksher, Erika; Burke, Wylie
Abstract: Shift work (working outside of 6:00 AM to 6:00 PM) is a fixture of our 24-hour economy, with approximately 18 per cent of workers in the USA engaging in shift work, many overnight. Since shift work has been linked to an increased risk for an array of serious maladies, including cardiometabolic disorders and cancer, and is done disproportionately by the poor and by minorities, shift work is a highly prevalent economic and occupational health disparity. Here we draw primarily on the state of science around shift work and breast cancer to argue that shift work represents a public health threat serious enough to warrant a precautionary stance. We use the precautionary principle to advance our case and view it as a moral compass for shift work research, empowering public health to cast shift work within the domain of health disparities deserving action despite scientific uncertainty. With the precautionary principle, we call for a deliberative decision-making process and formation of a broad shift work research collaboration to protect the health of many millions who work at night.